Mitigasi Bencana Longsor Sepanjang Jalan Penghubung dan Kawasan Sekitarnya dari Kota Pematang Siantar Menuju Kawasan Strategis Pariwisata Nasional Danau Toba - Pandapotan Sidabutar; Kasaman (Journal of Urban and Regional Development Studies, 2024)
Lake Toba tourism area is one of the National Tourism Strategic Areas (KSPN) based on Government Regulation Number 50 of 2011 concerning the National Tourism Development Master Plan 2010-2025, so it is a priority in tourism development. In supporting the increase in tourists, it is necessary to ensure accessibility to Lake Toba. The potential prone to natural disasters that often occur along the connecting road from Pematang Siantar City to the Lake Toba tourism strategic area has resulted in not a few casualties and material losses. Therefore, a mitigation strategy for potential landslides along the connecting road from Pematang Siantar city to Lake Toba National Tourism Strategic Area must be formulated properly. This research aims to analyze the risk of landslides along the connecting road and formulate a landslide mitigation strategy. The methods used include Geographic Information System (GIS) analysis to determine the level of landslide risk and SWOT analysis to formulate disaster mitigation strategies.. It is expected that the research method of landslide disaster risk mitigation activities for the distribution of disaster-prone areas along the connecting road will produce research results and recommendations that are useful for the academic world and practitioners in the development of connecting roads from Pematang Siantar city to the Lake Toba National Tourism Strategic Area including for local communities, entrepreneurs / investors / private sector, as well as the government and all stakeholders involved in the development of roads to KSPN.